KEARIFAN LOKAL SASTRA LISAN BATIMANG PADA MASYARAKAT DESA SIMALINYANG KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Siska Armiza; Hermansyah Hermansyah (Jurnal Ilmu Budaya, 2023)
This study aims to describe the values of local wisdom contained in the batimang oral literature by using the theory of Robert Sibarani so that the value of local wisdom is found in the batimang oral literature. The method used is a descriptive qualitative method with data collection techniques of observation, interviews and documentation. The results of the research obtained in the field show that there are six values of local wisdom in batiman oral literature, namely: hard work, education, preservation and cultural creativity, courtesy, harmony and conflict resolution and positive thinking. The local wisdom values obtained aim to achieve prosperity and peace in society.